Expression of p16 protein in breast cancer - Samman, Abdulhadi; Hanbazazh, Mehenaz; Samargandy, Saad; Al-Maghrabi, Jaudah (Polish Journal of Pathology, 2024)
Breast cancer is the most common cancer and a leading cause of death in women in Saudi Arabia. P16 is a tumour suppressor gene that plays a crucial role in regulating cell cycle. Several studies have investigated the significance of p16 expression in various cancer types. However, the significance of p16 in breast cancer remains controversial and insufficiently studied. The present study aims to examine the association between p16 expression and clinicopathological factors in breast cancer using immunohistochemistry staining. The study utilised 475 prospectively collected tissue samples from 475 women with breast cancer in Saudi Arabia. Nuclear and cytoplasmic immunohistochemical staining of p16 was observed in 338 (71%) of the cases and showed significant direct associations with adverse tumour features, including high tumour grade (p < 0.0001), negative oestrogen receptor/progesterone receptor status (p < 0.001), and lymph node metastasis (p = 0.02). Our study revealed a significant association between p16 protein expression and the established negative prognostic parameters in breast carcinoma including tumour grade, lymph node metastasis, and oestrogen receptor and progesterone receptor status.